Suboptimal culture conditions induce more deviations in gene expression in male than female bovine blastocysts. (December 2016) - Heras, Sonia; De Coninck, Dieter; Van Poucke, Mario; Goossens, Karen; Bogado Pascottini, Osvaldo; Van Nieuwerburgh, Filip; Deforce, Dieter; De Sutter, Petra; Leroy, Jo; Gutierrez-Adan, Alfonso; Peelman, Luc; Van Soom, Ann
Abstract Background Since the development of in vitro embryo production in cattle, different supplements have been added to culture media to support embryo development, with serum being the most popular. However, the addition of serum during embryo culture can induce high birthweights and low viability in calves (Large Offspring Syndrome). Analysis of global gene expression in bovine embryos produced under different conditions can provide valuable information to optimize culture media for in vitro embryo production. Results We used RNA sequencing to examine the effect of in vitro embryo production, in either serum-containing or serum-free media, on the global gene expression pattern of individual bovine blastocysts. Compared to in vivo derived embryos, embryos produced in serum-containing medium had five times more differentially expressed genes than embryos produced in serum-free conditions (1109 vs. 207). Importantly, in vitro production in the presence of serum appeared to have a different impact on the embryos according to their sex, with male embryos having three times more genes differentially expressed than their female counterparts (1283 vs. 456). On the contrary, male and female embryos produced in serum-free conditions showed the same number (191 vs. 192) of genes expressed differentially; however, only 44 of those genes were common in both comparisons. The pathways affected by in vitro production differed depending on the type of supplementation. For example, embryos produced in serum-containing conditions had a lower expression of genes related to metabolism while embryos produced in serum-free conditions showed aberrations in genes involved in lipid metabolism. Conclusions Serum supplementation had a major impact on the gene expression pattern of embryos, with male embryos being the most affected. The transcriptome of embryos produced in serum-free conditions showed a greater resemblance to that of in vivo derived embryos, although genes involved in lipid metabolism were altered. Male embryos appeared to be most affected by suboptimal in vitro culture, i.e. in the presence of serum.